Management of Students' Religious Culture - Rahmah, Syarifah; Ilham, Muhammad (Development: Studies in Educational Management and Leadership, 2022)
Being a religious person is everyone's dream, including a child's. Religious attitudes do not come instantly but through a process. Educational institutions such as schools are places where students' religious attitudes are formed. The participation of all elements, including parents and society, is the key to forming religious attitudes. The goal to be achieved in implementing this religious culture is so that students have good and polite personalities, can behave in the wider community and can be good examples. Appropriate methods and strategies must also be applied to create a sense of love for the Creator and enthusiasm for carrying out their human duties. Religious culture is one of the methods in value education, where teachers as uswah must carry out their duties properly because their learning achievement has only assessed the education that students get so far, so religion as the main foundation is increasing being abandoned, therefore the participation of various elements especially related institutions and teachers as key figures are needed.